1996
DOI: 10.1046/j.1365-2788.1996.802802.x
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic versus pituitary dysfunction in Down's syndrome as cause of growth retardation

Abstract: We have found that some children with Down's syndrome (DS) have growth retardation secondary to growth hormone (GH) deficiency. To test the hypothesis that hypothalamic dysfunction is the primary cause for GH deficiency and growth retardation, hypothalamic-pituitary responses of serum GH concentrations to levodopa and clonidine as well as pituitary responses in serum GH concentrations to growth-hormone-releasing hormone (GHRH) were analysed in 14 prepubertal children with DS. Levodopa and clonidine were given,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…In addition, these patients also have reduced pubertal growth spurt, contributing to the low final height [Cronk et al, 1988;Anner en et al, 1990]. It was demonstrated that children with DS do not have growth hormone (GH) deficiency [Anner en et al, 1986], but hypothalamic dysfunction was reported by Castells et al [1996]. A study performed by Anner en et al [1999] revealed that GH was given to children with DS increased growth velocity.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, these patients also have reduced pubertal growth spurt, contributing to the low final height [Cronk et al, 1988;Anner en et al, 1990]. It was demonstrated that children with DS do not have growth hormone (GH) deficiency [Anner en et al, 1986], but hypothalamic dysfunction was reported by Castells et al [1996]. A study performed by Anner en et al [1999] revealed that GH was given to children with DS increased growth velocity.…”
Section: Introductionmentioning
confidence: 99%
“…Growth hormone (GH) is known to have a major influence on statural growth by stimulating production of insulin‐like growth factor I (IGF‐I) from the age of 6–9 months, coinciding with the beginning of the pronounced growth retardation in DS. There is no evidence of a general GH deficiency in children with DS (4), but both suboptimal endogenous GH production (5) and selective deficiency of IGF‐I have been observed (6).…”
Section: Introductionmentioning
confidence: 99%
“…Detailed data on secretion of growth hormone (GH) in DS are largely lacking, although suboptimal GH production [2] and selective deficiency of insulin-like growth factor I (IGF-I) [3,4] have been reported in children with DS. Further, abnormalities (e.g.…”
Section: Introductionmentioning
confidence: 99%